Repair of fingertip defect with reverse digital artery island flap and repair of donor site with digital dorsal advancement flap - Ma, Junwei; Ding, Yunqi; Xu, Lina; Zou, Haibo; Wu, Jinsheng; Shen, Lin; Xing, Changtai; Liu, Yue; Zhou, Zehui; Zhan, Jie (Frontiers in Surgery, 2023)
Objective: The reverse digital artery island flap (RDAF) is widely used in repairing fingertip skin defects based on its good appearance and practicability. However, the donor area of the flap needs skin grafting, which can lead to complications. This retrospective study explored the clinical application of digital dorsal advance flap（DDAF）in repairing the donor site of the reverse digital artery island flap. Method: From June 2019 to February 2022, 17 patients with a soft tissue defect of the finger had been restored with the reverse digital artery island flap，and at the same time, the donor area was repaired with digital dorsal advance flap（DDAF）. The sensitivity，the active range of motion (ROM) and patient satisfaction were assessed after the operation. Results: All flaps survived completely without skin grafting with only one linear scar. The sensory and motor functions of all patients recovered well. Assessment based on the Michigan Hand Outcomes Questionnaire (MHQ) showed satisfactory functional recovery for all patients. Conclusions: Reconstruction using RDAF combined with DDAF represents an effective alternative for repairing fingertip skin defects.